Legal Analysis of Savings and Loan Cooperatives with Money Laundering with the Origin of Fraud Together and Continues in Decision No. 2113 K / Pid.Sus/2023 - Sitompul, Ariman (International Asia Of Law and Money Laundering, 2026)
Money laundering is a complex organized crime with a growing modus operandi and threatens the stability of the national financial system, particularly involving non-bank financial institutions such as poorly regulated savings and loan cooperatives. This study analyzed the Supreme Court Decision No. 2113 K/PID.SUS/2023 uses normative juridical methods with statute and case study approaches to assess the criminal responsibility of individuals and corporations in money laundering originating from continuing fraud, and identify the effectiveness of preventive legal mechanisms through supervision of savings and loan cooperatives in the context of criminal law enforcement. The results showed that the criminal liability of the perpetrator has met the theory of Identification and Strict Liability with evidence of systematic transactions, but the application of criminal sanctions by the panel of judges is still not in accordance with the maximum provisions of Article 7 of law no. 8 of 2010 and Article 121 of Law No. 1 year 2023. The Supervisory Mechanism of savings and loan cooperatives shows structural weaknesses in the implementation of Know Your Customer and Customer Due Diligence principles, as well as the absence of a mandatory and standardized Suspicious Transaction Reporting System. The study concluded that a comprehensive regulatory reform, strengthening the capacity of law enforcement officers, and strengthening surveillance systems are needed to improve the effectiveness of combating money laundering in the cooperative sector